2016
DOI: 10.1155/2016/4270301
|View full text |Cite
|
Sign up to set email alerts
|

The Adenosinergic System in Diabetic Retinopathy

Abstract: The neurodegenerative and inflammatory environment that is prevalent in the diabetic eye is a key player in the development and progression of diabetic retinopathy. The adenosinergic system is widely regarded as a significant modulator of neurotransmission and the inflammatory response, through the actions of the four types of adenosine receptors (A1R, A2AR, A2BR, and A3R), and thus could be revealed as a potential player in the events unfolding in the early stages of diabetic retinopathy. Herein, we review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…However, the reported effects of diabetic conditions on purinergic receptor expression in different tissues are multiple and complex. An alteration in purinergic receptor subtype expression patterns has been observed in diabetes in the retina and other tissues (Ho et al, ; Kneer, Green, Meyer, Rich, & Minns, ; Mankus, Rich, Minns, & Trinkaus‐randall, ; Seref‐ferlengez, Maung, Schaffler, & Spray, ; Vindeirinho, Santiago, Cavadas, Ambrósio, & Santos, ). For example, in diabetic animals, an increase in levels of P2X 7 R has been reported in corneal epithelium (Kneer et al, ; Mankus et al, ), although a decrease in the expression of these receptors also was shown in osteocytes under HG conditions (Seref‐ferlengez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported effects of diabetic conditions on purinergic receptor expression in different tissues are multiple and complex. An alteration in purinergic receptor subtype expression patterns has been observed in diabetes in the retina and other tissues (Ho et al, ; Kneer, Green, Meyer, Rich, & Minns, ; Mankus, Rich, Minns, & Trinkaus‐randall, ; Seref‐ferlengez, Maung, Schaffler, & Spray, ; Vindeirinho, Santiago, Cavadas, Ambrósio, & Santos, ). For example, in diabetic animals, an increase in levels of P2X 7 R has been reported in corneal epithelium (Kneer et al, ; Mankus et al, ), although a decrease in the expression of these receptors also was shown in osteocytes under HG conditions (Seref‐ferlengez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy is one of the most common complications associated with diabetes and one of the major causes of adult blindness (International Diabetes Federation, ). The mechanisms that are involved in this condition include damaged retinal vasculature, neurodegeneration, and inflammation (Jonsson et al ., ; Vindeirinho et al ., ). Ocular imaging techniques are very important for diagnosis and the evaluation of treatment efficacy (Tan et al ., ).…”
Section: Retinopathymentioning
confidence: 97%
“…Several reviews about purinergic signalling in diabetes and its therapeutic potential are available ( Burnstock and Novak, 2013 ; Cieslak and Roszek, 2014 ; Antonioli et al, 2015 ; Fotino et al, 2015 ; Kishore et al, 2015 ; Merighi et al, 2015 ; Vindeirinho et al, 2016 ). The involvement of purinergic signalling in diabetic nephropathy is discussed later in the Section on Kidney.…”
Section: Endocrine Diseasesmentioning
confidence: 99%